If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+(9 x-4)=18
We simplify the equation to the form, which is simple to understand
2x+(9x-4)=18
Remove unnecessary parentheses
+2x+9x-4=+18
We move all terms containing x to the left and all other terms to the right.
+2x+9x=+18+4
We simplify left and right side of the equation.
+11x=+22
We divide both sides of the equation by 11 to get x.
x=2
| 6.8x-3=5.8x | | 2m-7.5=5.8 | | X*386000=2512000 | | 3(5f+6)= | | X=-1-1*2 | | 8-4z=20 | | 4(z+7)-(2z-1)=z | | 8x-2x(x-9)=2(x-5)+1 | | X=-1-1*-1 | | 2/x-3=26/x | | 4(z+7)-(2x-1)=z | | 4c^2+19c-21=0 | | X=-8-1*-1 | | 16-(4M+8)=5+4M-13 | | (-1)-2*6= | | X=-8-y | | 3/4v=6 | | 6-8-(-12)-14-3*3*2*2= | | 5x+b=192 | | (-4)+(-2)*(-3)= | | 0=0.25x^2-5x+80 | | y=0.25x^2-5x+80 | | (-6)-(-10)= | | 0.8q+q=8(0.6q-2) | | 4x+2y+7+4x+3y= | | f(-1)=2x-3x | | 2x^2+x+1=25 | | 5y+y=90 | | 6-4(2-5x)= | | 8(m+3)=4 | | 11+5x=4x-20 | | log[2](-6-5x)=2 |